In Situ Synthesis of Hypercrosslinked Polymer as Stationary Phase for Capillary Gas Chromatography - Yan Wu; Chaofan Song; Guanwen Huang; Kaicheng Wu; Yinghong Zhao; Ailin Ning; Wenlanqi Du; Jia Jia (Separations)
Hypercrosslinked polymers (HCPs) constructed by the Friedel–Crafts alkylation reaction of aromatic compounds have emerged as a new class of porous materials with unique merit. Herein, a HCP named HCP-TPB was coated onto a capillary column through in situ synthesis. The prepared column exhibited a nonpolar nature, and the column efficiency for n-dodecane was 3003 plates m−1. Moreover, the relative standard deviations of retention time and peak area for six replicate injections of the C3–C6 were lower than 0.1% and 1.5%, respectively. The results of this study showed that it is very promising to utilize HCPs as stationary phases for the separation of C3–C6.